Expert Evaluation of the Expression of Personal Competencies in Professional Activities - Kunskaja, Svetlana (European Journal of Economics and Business Studies, 2018)
The analysis of scientific literature provides basis for the relevance of personal competence, focusing on the development of individual’s opportunities in professional activities. A new modern approach to personal development is associated with learning and development; health, wellness and safe workplaces; human resources measurement, reporting and financial management and empowering competencies/individual skills, comprising critical thinking and analysis; technology knowledge; research capabilities; quantitative and critical legal thinking capabilities. For the purpose of identifying the relevance of personal competencies in professional activities, an expert evaluation of the energy and environmental sectors was conducted. Summary results of the research of personal competencies in professional activities is presented in an expert evaluation model, distinguishing between the most significant and the least significant components. Non-parametric tests and calculation of the concordance of expert opinions by means of the Kendall concordance coefficient W and H0 hypothesis tests determine good and very good concordance of expert opinions in all cases.